SOLVe: a closed-loop system focused on protective mechanical ventilation - von Platen, Philip; Pickerodt, Philipp A.; Russ, Martin; Taher, Mahdi; Hinken, Lea; Braun, Wolfgang; Köbrich, Rainer; Pomprapa, Anake; Francis, Roland C. E.; Leonhardt, Steffen; Walter, Marian (Biomedical engineering online, 2023)
Mechanical ventilation is an essential component in the treatment of patients with acute respiratory distress syndrome. Prompt adaptation of the settings of a ventilator to the variable needs of patients is essential to ensure personalised and protective ventilation. Still, it is challenging and time-consuming for the therapist at the bedside. In addition, general implementation barriers hinder the timely incorporation of new evidence from clinical studies into routine clinical practice. We present a system combing clinical evidence and expert knowledge within a physiological closed-loop control structure for mechanical ventilation. The system includes multiple controllers to support adequate gas exchange while adhering to multiple evidence-based components of lung protective ventilation. We performed a pilot study on three animals with an induced ARDS. The system achieved a time-in-target of over 75 % for all targets and avoided any critical phases of low oxygen saturation, despite provoked disturbances such as disconnections from the ventilator and positional changes of the subject. The presented system can provide personalised and lung-protective ventilation and reduce clinician workload in clinical practice.